Really effective (for 15% of the men): Lessons in understanding and addressing user needs in climate services from Mali - Carr, Edward R.; Onzere, Sheila N. (Elsevier, 2018)
Climate services have long been held up as development tools with tremendous potential to reduce risk and vulnerability, and build resilience, for agrarian communities in the Global South (Dessai et al., 2009, Fröde et al., 2013, Pervin et al., 2013, USAID Global Climate Change Office, 2014). The ongoing development and refinement of climate service-based tools, such as weather based index insurance, provides opportunities to stabilize and protect people’s livelihoods by establishing new forms of safety nets, strengthening existing safety nets, and supporting the general improvement of risk management mechanisms (Carter et al., 2014, Hess and Syroka, 2005, Jensen et al., 2015, Mburu et al., 2015). For example, climate advisories and information offer opportunities to inform farmer management of climate related risk (Boyd et al., 2013, Carr et al., 2015c, Hansen, 2012, Hellmuth et al., 2011, Ingram et al., 2002), such as by supporting farmer decisions with regard to intensifying production, investing in new technologies, or taking measures to protect their households and livelihoods in the case of adverse predictions (Carr et al., 2015a, Carr et al., 2015c, Hansen, 2012).